Why do nurses intend to leave their organization? A large-scale analysis in long-term care - Tummers, Lars G.; Groeneveld, Sandra M.; Lankhaar, Marcel (Journal of advanced nursing, 2013)
Aim To analyse the impact of six job characteristics on the intention of nurses to leave their organization, specifically focusing on long‐term care settings: nursing homes, care homes and home care. Background When nurses leave their organization, this can negatively affect organizational performance. Organizations have to recruit new nurses and tacit knowledge is lost. Furthermore, organizational turnover could contribute to the nursing shortage, which will increasingly become a problem given the ageing population. This article adds to the literature, given: (a) its focus on long‐term care; and (b) by explicating the differences between nursing and care homes (intramural) on one hand and home care (extramural) on the other. Design Survey. Method Survey of 9982 nurses in 156 Dutch organizations in 2010–2011, 6321 nurses in nursing and care homes and 3661 nurses working in home care, based on the ActiZ Benchmark in Healthcare. Results First, the most important reason for nurses’ intention to leave is insufficient development and career opportunities. Secondly, a negative working atmosphere strongly influenced intention to leave. The impact of the working atmosphere is not often examined in the literature. However, this research shows that it is an important reason. Thirdly, intention to leave is partly context dependent. More specifically, when nurses in home care felt that their autonomy was reduced, this strongly influenced their intention to leave, although this was not the case for nurses working in nursing and care homes. Conclusion This article provides guidelines for organizations on how to retain their nurses.